Conditional Wwox Deletion in Mouse Mammary Gland by Means of Two Cre Recombinase Approaches - Ferguson, Brent W. (Public Library of Science, 2012)
Loss of WWOX expression has been reported in many different cancers including breast cancer. Elucidating the function of this gene in adult tissues has not been possible with full Wwox knockout models. Here we characterize the first conditional models of Wwox ablation in mouse mammary epithelium utilizing two transgenic lines expressing Cre recombinase, keratin 5-Cre (BK5-Cre) and MMTV-Cre. In the BK5-Cre model we observed very efficient Wwox ablation in KO mammary glands. However, BK5-Cre Wwox KO animals die prematurely for unknown reasons. In the MMTV-Cre model we observed significant ablation of Wwox in mammary epithelium with no effect on survival. In both of these models we found that Wwox deletion resulted in impaired mammary branching morphogenesis. We demonstrate that loss of Wwox is not carcinogenic in our KO models. Furthermore, no evidence of increase proliferation or development of premalignant lesions was observed. In none of the models did loss of a single Wwox allele (i.e. haploinsufficiency) have any observable phenotypic effect in mammary gland. To better understand the function of Wwox in the mammary gland, transcriptome profiling was performed. We observed that Wwox ablation results in the deregulation of genes involved in various cellular processes. We found that expression of the non-canonical Wnt ligand, Wnt5a, was significantly upregulated in Wwox KO mammary epithelium. Interestingly, we also determined that components of the Jak/Stat3 signaling pathway were upregulated in KO mice and this correlated with a very robust increase in phospho-Stat3 signaling, which warrants further testing. Even though the loss of Wwox expression in breast and other cancers is very well documented, our findings suggest that Wwox does not act as a classical tumor suppressor as previously thought.